1996
DOI: 10.1007/bf02786257
|View full text |Cite
|
Sign up to set email alerts
|

Serum protein and zinc levels in patients with thoracic empyema

Abstract: The element Zn is the metal component or activator of many important enzymes. The tissue concentrations and activities of Zn metalloenzymes direct the rate of protein and nucleic acid syntheses, thereby influencing tissue growth and reperative processes. Most of the serum Zn is normally bound to circulating proteins. Low serum Zn concentrations might result from depletion of Zn-binding proteins. Serum protein and Zn concentrations have been reported to be depressed in patients with acute and chronic diseases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…17 An assessment can be made by measuring the level of various biochemical parameters in body fluids, such as serum or plasma. 9 Cu and/or Zn levels in serum/plasma are quite often used to investigate the effectiveness of an ongoing anti-tubercular or thoracic emphysema therapy 18 . Furthermore, their levels in tissues 19,20 or in serum 19,21 are used in the diagnosis process of lung affections including TB, or in the assessment of risk factors for the development of carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…17 An assessment can be made by measuring the level of various biochemical parameters in body fluids, such as serum or plasma. 9 Cu and/or Zn levels in serum/plasma are quite often used to investigate the effectiveness of an ongoing anti-tubercular or thoracic emphysema therapy 18 . Furthermore, their levels in tissues 19,20 or in serum 19,21 are used in the diagnosis process of lung affections including TB, or in the assessment of risk factors for the development of carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Zn is involved in wound healing and immunity, and functions as an antioxidant. Balkan et al 13 found that serum Zn and protein levels were low in patients with empyema, both increasing in those who received Zn replacement. The reasons for elevated Zn in infection‐related effusions are unknown.…”
Section: Discussionmentioning
confidence: 99%